Islamic Republic of Afghanistan : Second Review Under the Staff-Monitored Program-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses economic developments, outlooks, and risks in Afghanistan. The economy is in difficultly. Deepening uncertainty about the political transition following the 2014 presidential election, corruption and weak governance, and a weakening security environment have complicated the implementation of reforms, undermined confidence and economic activity, and contributed to increased emigration. The overall budget had a deficit in 2015 as a shortfall in grants more than offset higher-than-projected revenue and lower spending. The trade deficit remained large, but substantial inflows of foreign aid kept the current account in surplus. The financial sector remains fragile and plays a limited intermediation role.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet